2019
DOI: 10.3390/cells8090967
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Metabolic Reprogramming in Acute Myeloid Leukemia

Abstract: The cancer metabolic reprogramming allows the maintenance of tumor proliferation, expansion and survival by altering key bioenergetics, biosynthetic and redox functions to meet the higher demands of tumor cells. In addition, several metabolites are also needed to perform signaling functions that further promote tumor growth and progression. These metabolic alterations have been exploited in different cancers, including acute myeloid leukemia, as novel therapeutic strategies both in preclinical models and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 139 publications
0
46
0
Order By: Relevance
“…The metabolic status of AML cells can also be influenced by the amount of nutrients and metabolites in their microenvironment [9,10,46,60]. Modulation of systemic metabolic profiles may therefore be a strategy that indirectly affects the AML cells through alteration of their microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic status of AML cells can also be influenced by the amount of nutrients and metabolites in their microenvironment [9,10,46,60]. Modulation of systemic metabolic profiles may therefore be a strategy that indirectly affects the AML cells through alteration of their microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Complex metabolic capacities may contribute to the aggressiveness of AML, allowing cells to survive under higher metabolic demands. However, AML patients are heterogeneous with regard to metabolic regulation [8][9][10][11][12] and in this study we attempt to further investigate if patients are heterogeneous also with regard to the antileukemic effects of metabolic targeting.…”
Section: Introductionmentioning
confidence: 99%
“…A large clinical study showed that the systemic levels of 14 glucose metabolites could be used to identify patients with an increased risk of later leukemia relapse [ 51 ]. Other studies also suggest that the AML cell metabolism and not only the systemic metabolic regulation differ between AML patients [ 48 , 67 , 68 ], but the possible prognostic impact of such differences needs further investigation.…”
Section: Aml Heterogeneity and Prognostic Evaluationmentioning
confidence: 99%
“…Metabolic reprogramming is recognized as a hallmark of cancer (184,185) and targeting metabolic pathways has been used for the treatment of various cancers to interfere with tumor progression (184,186). During bacterial infections of the lung the metabolic pathways of many immune cells are re-programmed to a more immunosuppressive phenotype, benefitting the bacteria and leading to chronic infection.…”
Section: Targeting Metabolic Changes Induced During Infectionmentioning
confidence: 99%